USING ONCE UPON A TIME TO IMPROVE THE NARRATIVE TEXT WRITING SKILL OF THE TENTH GRADERS OF SMA EL SHADAI MAGELANG IN THE SCHOOL YEAR 2018/2019 - Indah Adha Rizkalillah (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2020)
In this globalization era English has been used as a means of communication among the nation all over the world.Writing is one of language skills to inform an idea from the writer to the reader. Based on the writer’s observation, writing is difficult enough to be developed by the tenth graders of SMA El Shadai Magelang. It can also be proved by their the average score of writing skill is under the standard minimum score that is 78.The purpose of this research is to improve the students’ writing skill using Once Upon a Time game. There are two objectives of this research. The first one is to know whether the use of Once Upon a Time game can improve the learning motivation of the narrative text writing skill and the second is to know how great the improvement of the narrative text writing skill who are taught by using Once Upon a Time game.The type of this research is an action research. It means that action research will be conducted to improve and make up learning condition and situation in order to make something better than before that will be repeated in Cycle procedures. The subject of this research is the tenth graders of SMA El Shadai Magelang in the school year 2018/2019. The writer chooses one class as the subject that is X-IPS that consist of 12 students. To analyze the data, the writer uses quantitative and qualitative data. Keywords :Once Upon a Time game, writing skill, narrative text, AR